Vegetal cover change evaluation in Quillcay river sub-basin using normalized difference vegetation index (Aporte Santiaguino, 2024)
In the Quillcay River sub-basin, located in the province of Huaraz, Áncash, Peru, changes in high Andean ecosystems are evident, represented by typical plant communities due to anthropogenic pressure. To evaluate these changes in the period 1987-2023, the normalized difference vegetation index (NDVI), Landsat L2SP TM OLI images and field work were used. It was observed that the NDVI increased in the lower part of the sub-basin due to the installation of exotic forest plantations in the buffer zone of the Huascarán National Park. In this park, the NDVI changes were negative in areas with high Andean grasslands and wetlands where various anthropogenic activities take place.
Keywords: NDVI; Landsat; wetlands; anthropogenic activity; Andean ecosystems